2005
DOI: 10.1007/s00467-005-1976-8
|View full text |Cite
|
Sign up to set email alerts
|

Community-acquired enterococcal urinary tract infections

Abstract: Enterococcal urinary tract infection (UTI) is usually hospital-acquired and affects individuals with predisposing conditions. The aim of this study was to evaluate the community-acquired enterococcal UTIs in otherwise well children. We reviewed all the 257 first UTI episodes in children hospitalized in a General Hospital during a 5-year period. Enterococcus faecalis was isolated in 13 episodes, accounting for 5.1% of the total UTIs. All strains were susceptible to ampicillin, vancomycin and nitrofurantoin. Ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
32
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 15 publications
4
32
1
Order By: Relevance
“…These observations have practical implications, as detailed below. The relative frequency of CA enterococcal UTIs found in our study, 6.2% of all episodes of UTI, is slightly higher than the rates reported by others, which ranged from 4.4 to 5.6% [24,26]. This difference may reflect the fact that the pediatric nephrology and pediatric urology services in our tertiary center receive referrals from a wide geographical area.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…These observations have practical implications, as detailed below. The relative frequency of CA enterococcal UTIs found in our study, 6.2% of all episodes of UTI, is slightly higher than the rates reported by others, which ranged from 4.4 to 5.6% [24,26]. This difference may reflect the fact that the pediatric nephrology and pediatric urology services in our tertiary center receive referrals from a wide geographical area.…”
Section: Discussioncontrasting
confidence: 81%
“…Of the less common Gram-positive pediatric uropathogens, the main genus is Enterococcus, predominantly the species Enterococcus faecalis [10]. However, research on enterococcal UTIs in children is very limited, with most studies dealing with nosocomial infections [21][22][23][24]. Due to its unique antimicrobial susceptibility profile, Enterococcus spp.…”
Section: Introductionmentioning
confidence: 99%
“…Ashkenazi et al [3] showed that urinary tract malformation and urinary catheterization were associated with PA UTI in six children with communityacquired and 12 children with nosocomial infections. Bitsori et al [10] compared 13 children with community-acquired enterococcal (E. faecalis) UTI with 243 patients with gramnegative UTI (patients with PA UTI were not included in their control group). Similarly to our results, patients with enterococcal UTI had significantly more urinary tract abnormalities and urinary tract surgery.…”
Section: Discussionmentioning
confidence: 99%
“…It is well-known that enterococcal-caused urinary tract infections are more frequent prior to 10 years of age and after 60 years of age when genitourinary anomalies and obstructive uropathy are more frequent [19]. Interestingly, Bitsori et al [20] studied community-acquired enterococcal urinary tract infection in children and reported a high rate of anatomical abnormalities of the urinary tract and a poorer prognosis with respect to renal scarring. These investigators concluded that enterococcal urinary tract infection in children is highly indicative of urinary tract abnormalities and related complications.…”
Section: Discussionmentioning
confidence: 99%